EXPRESSION OF NATIONAL REALIA IN LITERARY TEXTS - Kazakova Nodira Davlatovna (International Scientific and Current Research Conferences, 2025)
This thesis explores the ways national realia are represented in literary texts and examines their role in conveying cultural identity and social experience. National realia refer to culture-bound elements embedded in language that reflect a nation’s historical background, everyday practices, and value systems. The study focuses on how literary authors employ such elements to construct meaning, enhance realism, and preserve national distinctiveness. The analysis demonstrates that national realia function not merely as descriptive details but as integral components of narrative structure that shape interpretation and reader perception. The findings confirm that the artistic use of national realia strengthens the connection between literature and national consciousness.